Efeitos da sobrecarga crônica de ferro sobre a estrutura/função vascular de camundongos ateroscleróticos - Marques, Vinicius Bermond (2019)
Iron is an essential metal for cellular homeostasis, but when overloaded it has been associated with damage to various organs, including the cardiovascular system. We previously demonstrated in rats that iron overload induces endothelial dysfunction and oxidative stress, which could increase the risk of atherosclerosis. However, the iron related harmfulness under a genetic predisposition to atherosclerosis is still unclear. In this study we have tested the hypothesis that chronic iron overload intensifies the atherosclerotic process associated with endothelial dysfunction in apolipoprotein E knockout mice (apoE(-/-)). Serum and aortas of wild-type C57BL/6 (C57) and apoE(-/ ) mice injected with saline or ferro-dextran i.p. (Fe, 10 mg/mouse/day) 5 times a week for 4 weeks were used. Iron overload increased serum iron levels and biomarkers of liver injury and oxidative stress, as well as aortic iron deposition in both lines, but only apoE(-/-) Fe mice had intensified hypercholesterolemia (1.7 times), the size of the atherosclerotic plaque (19% of the aortic lumen) and the cellular infiltrate in these lesions. By scanning electron microscopy, the small endothelial structural damage caused by iron in C57 was worsened in the apoE(-/-) Fe group. However, endothelial dysfunction was found only in the apoE(-/-) Fe group, identified by impaired relaxation to acetylcholine and hyperreactivity to phenylephrine associated with reduced nitric oxide modulation. Moreover, tiron and indomethacin attenuated reactivity to phenylephrine with greater magnitude in aortas of the apoE(-/-) Fe group. Confirming, there were reduces in the antioxidant (superoxide dismutase and catalase) activity, increased expression of cyclooxygenase-2 in the aorta and elevated levels of thromboxane A2 and prostacyclin metabolites in the urine of apoE(-/-) Fe group. Our results showed that chronic iron overload intensifies the atherosclerotic process and induces endothelial dysfunction in atherosclerotic mice, probably due to the oxidative stress and the imbalance between the relaxing and contractile factors synthesized by the damaged endothelium.